PENGARUH PERCEIVED QUALITY TERHADAP BRAND LOYALTY MELALUI MEDIASI BRAND IMAGE DAN BRAND TRUST - Hironimus Hari Kurniawan (Jurnal Bisnis dan Manajemen, 2017)
McDonald’s is one of the most popular fast food restaurant in Indonesia that faces a declining trend in the Top Brand Index continues. It happens while food and beverage industry is growing significantly, especially in Malang. The peak of this research is brand loyalty as the most strategic intangible asset in order to dominate market share while industry competition increase. The purpose of this research is to find the influence of perceived quality to brand image, brand trust and brand loyalty, the influence of brand image and brand trust to brand loyalty, then the mediation of brand image and brand trust in the relationship between perceived quality to brand loyalty. A sample of this research has taken online with purposive sampling method and it used 150 respondents. The collected data analyzed in PLS (Partial Least Square) technique with Smart PLS 3 software. The mediation variables, hypothesis tested with Sobel. The finding of this research indicates that perceived quality positive and significantly influence to brand image, brand trust and brand loyalty. Then brand image and brand trust positive and significant influence to brand loyalty. Brand image and brand trust found as mediating variables in the relationship perceived quality to brand loyalty. Brand image has the highest influence to McDonald’s brand loyalty, especially in Malang. DOI : https://doi.org/10.26905/jbm.v4i2.1703